Assessment of the Awareness of Knowledge of Dental Records in Forensic Dentistry among Undergraduate Dental Students - Shyam Sundar Behura1, Shirsha Mukherjee2, Roquaiya Nishat3, Lipsa Bhuyan4, N Aravindha Babu5 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Aim & Objectives: To assess the awareness of patient’s dental record maintenance among BDS students and to evaluate their knowledge regarding the potential use of their maintained records in forensic identification.Materials and Method: Data was collected by means of a self administered questionnaire consisting of 24 closed ended questions, addressed on the awareness about patient’s dental record maintenance and its importance in forensic needs among 3rd, 4th year BDS students and interns of a private dental college.Results: 73.1% of the respondents were aware that dentists were legally bound to maintain records in India and 83.5% were aware that these could contribute towards forensic investigations. Most of the students were aware of how to maintain dental records in an institution. 67.4% of the study population felt the need to store records for a minimum of 5 years. 65-70% had knowledge regarding denture markers and role of implants in forensic identification. The most perceived barrier to good dental record keeping was lack of time according to most of the students.Conclusion: The survey revealed awareness on the importance of dental records in forensic identification among BDS students. Few areas showed inadequate knowledge, thus mandating an utmost need to train dental students in this field. Newer methods like denture marking and Aadhar number in corpoartion in prostheses should be given importance.